2009
DOI: 10.2174/1876894600901010050
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Synovial Microparticles as Revealed by Atomic Force and Scanning Electron Microscope

Abstract: Abstract:Microvesicles which are pinched off the cell membrane can be considered extracellular organelles which mediate interaction between distal cells. They were suggested to play an important role in many diseases including autoimmune disorders, however, standard methods for their assessment have not yet been decided upon while their clinical relevance and the underlying mechanisms are yet unclear. We present a pilot study results involving atomic force microscope (AFM) and scanning electron microscope (SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…17,18 Information on the presence of tumors could be obtained from cell-derived nanovesicles which are expected to be found in body fluids, such as blood, synovial fluid, ascites, pleural fluid, and cerebrospinal fluid. 19,20 For example, it was recently demonstrated that tumors of various origin 21 and various clinical outcomes 22 can be classified by their micro RNA (miRNA) profiles. miRNAs are short (about 18-25 nucleotides long) noncoding RNAs, including small interfering RNA, ribosomal RNA, transfer RNA, and small nuclear RNA.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Information on the presence of tumors could be obtained from cell-derived nanovesicles which are expected to be found in body fluids, such as blood, synovial fluid, ascites, pleural fluid, and cerebrospinal fluid. 19,20 For example, it was recently demonstrated that tumors of various origin 21 and various clinical outcomes 22 can be classified by their micro RNA (miRNA) profiles. miRNAs are short (about 18-25 nucleotides long) noncoding RNAs, including small interfering RNA, ribosomal RNA, transfer RNA, and small nuclear RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Vesiculation was studied in cancer cells [9][10][11][12][13] and was shown in vivo to be connected to the impact of cancer-associated coagulopathies. [14][15][16][17] Furthermore, nanoparticles have also been found in isolates from other body fluids, such as synovial fluid of inflamed joints, 18 pleural fluid, 19 ascites, 19 saliva, 20,21 and urine.…”
Section: Introductionmentioning
confidence: 99%
“…Visualization of the isolates obtained by this protocole by the scanning electron microscope and by atomic force microscope (Junkar et al, 2009) revealed shapes that are characteristic for particles without internal structure (such as discocytes, dumbbell shapes and "starfish" shapes (Seifert, 1997) that correspond to the minima of the membrane free energy at different ratios between membrane area and enclosed volume …”
Section: Accepted Manuscriptmentioning
confidence: 99%